2009
DOI: 10.3109/08923970903124627
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of zinc oxide on Th2 but not Th1 immune responses in mice

Abstract: These results suggest that ZnO appears to have an adjuvant effect on the immune system, especially Th2 but not Th1 immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…This suggests that oral tolerance induced by the mucosal immune system in the gut might be modulated by such very small size of particles. In addition, our recent studies revealed that treatment of mice with ultrafine ZnO was followed by the enhancement of immune responses, especially on T H 2 responses (Matsumura et al, 2010). The similar adjuvant effect was observed when mice were exposed to DEP (Yoshino and Sagai, 1999).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…This suggests that oral tolerance induced by the mucosal immune system in the gut might be modulated by such very small size of particles. In addition, our recent studies revealed that treatment of mice with ultrafine ZnO was followed by the enhancement of immune responses, especially on T H 2 responses (Matsumura et al, 2010). The similar adjuvant effect was observed when mice were exposed to DEP (Yoshino and Sagai, 1999).…”
Section: Discussionsupporting
confidence: 49%
“…Yoshino and Sagai (1999) demonstrated that mice exposed to DEP had enhanced production of HELspecific IgG 2a and IgG 1 that was associated with increased secretion of IFNγ and IL-4, respectively, suggesting that DEP appears to have adjuvant activity on both T H 1 and T H 2 immune responses. On the other hand, Matsumura et al (2010) revealed that treatment of mice with OVA plus ZnO was followed by greater increases in anti-OVA IgG 1 /-IgE and IL-4/IL-5, but not in anti-OVA IgG 2a and IFNγ compared with that with OVA alone, indicating that ZnO seems to selectively stimulate T H 2 but not T H 1 responses. The blockade of induction of oral tolerance by DEP was associated with marked prevention of the suppression of both T H 1 and T H 2 secretion by oral antigen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The assay to measure OVA-specific antibodies was performed as described previously (Matsumura et al 2010). IgG, IgG 1 , IgG 2a , and IgE antibodies specific for OVA were each measured by ELISA.…”
Section: Measurement Of Ova-specific Antibodiesmentioning
confidence: 99%
“…Aggravation of asthma is unlikely to be caused by cytotoxicity of the NPs because exposure by the respiratory tract and by other routes (subcutaneous, intraperitoneal), where no direct contact with the alveolar epithelium occurred, caused the same effects. [113][114][115] The mechanisms for amplifying pre-existing pathologies have been proposed through the following mechanisms:…”
mentioning
confidence: 99%